Gamma delta T-cells - Silva-Santos, Bruno (Henry Stewart Talks, 2022)
γδ T cell biology, Butyrophilins are key regulators of γδ T cell activity, Vδ2+ γδ T cell differentiation, Antitumor functions of γδ T cells, γδ T cells in the peripheral tissues, γδ T cells in infection and inflammation